Still life: a poetic and photographic reflection - Menegazzo, Maria Adélia (Lumina - Revista do Programa de Pós-Graduação em Comunicação da Universidade Federal de Juiz de Fora, 2015)
Born as a gender of the Dutch painting of the 16th century, still life served to both a merely decorative taste and the need of deep reflections about the ephemerality of the human presence in the world. While vanitas had as a function to recollect that pleasures and appearances are ephemeral; while memento mori induced to reflection about life and death, reaching in both the forms and the allegorical character. Since the early days of photography, the model is the painting, and the theme of still life appears both in classics like Talbot and Bayard, and in modern Rodchenko and Cartier-Bresson. In the Brazilian modernist poetry, the reading of “Maçã”, by Manuel Bandeira, has already become classical as a cubist still life. Our work aims to investigate settings that the theme finds in the contemporary poetry of Paulo Henriques Brito and Ana Martins Marques, as well as in photographs of Robert Frank and Francesca Woodmann and in a video of Sam Taylor Wood, enhancing its indexical, allegorical and narrative character.